Perception of the use of telemedicine during the health emergency caused by COVID-19 in obstetrics professionals - Mera-Yauri, Andrea Karla (2023)
Introduction: In March 2020, the World Health Organization declared COVID-19 a pandemic. As a result, healthcare systems chose to suspend in-person outpatient visits to reduce exposure. This situation had an impact on maternal health services and sexual and reproductive health, leading to the implementation of telemedicine to ensure continuity of care. Telemedicine, being a new care model, has its limitations, but to guarantee its successful implementation and application, it is necessary to understand the perception of healthcare professionals who will use it. Objective: To determine the perception of the use of telemedicine during the COVID-19 health emergency in obstetrics professionals. Materials and Methods: This study had a quantitative, observational, descriptive, and cross-sectional approach, conducted with 40 obstetricians working in telemedicine. Information was collected through a survey using a valid and reliable Likert scale instrument. Results: 80.0% of obstetricians used cell phones to carry out telemedicine consultations. 42.5% stated that the activities scheduled for professionals participating in different areas of care were not aligned and coordinated. Regarding the telemedicine platform used for patient care, 57.5% of obstetricians found it user-friendly. Additionally, 35.0% considered that telemedicine maintains timely access to healthcare services for the population, and 45.0% of obstetricians indicated that it empowers users for self-care. Conclusions: In the perception of telemedicine use among obstetrics professionals, it was found that 65.0% of obstetricians have a moderately favorable perception, followed by 35.0% with a favorable perception. This indicates the need to strengthen the implementation processes of telemedicine.